Physical Quality of Drying Curcuma Products as Raw Material for Curcuma Herbal Dip - Ning Puji Lestari; Syifa Putri Rafika Wati; Nur Ida Winni Yosika; Iwan Taruna; Dian Purbasari; Sutarsi (Universitas Brawijaya, 2026)
Curcuma is a rhizome widely used as herbal medicine due to its various health benefits, including increasing appetite and promoting overall health. Herbal medicine in liquid form has a limited shelf life at room temperature and specific refrigeration temperatures. These limitations make traditional herbal medicine difficult to reach a broader market, necessitating alternatives with longer shelf lives, such as herbal tea bags. This study was conducted to investigate the drying of curcuma into curcuma powder packaged in filter paper, making it more convenient for brewing and longer-lasting. The drying of curcuma in this study utilized a microwave. In addition to being influenced by microwave power, the quality of curcuma dissolution is also affected by geometric shape variability. The results of the study showed bulk density values between 0.54-0.61 g/mL; solubility values of 99.56-99.62%; moisture content of 9-11.33%; brightness levels of 21.05-28.96; redness levels of 1.42-2.53; and yellowness levels of 5.00-6.41. Microwave power significantly influenced all parameters, while geometric shape only affected brightness, redness, and yellowness. The best treatment combination is 3.49 mm (medium) and microwave power of 322 W (low).